2018
DOI: 10.1186/s12886-018-0979-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to face-down and non-supine positioning after macular hole surgery

Abstract: BackgroundThis study aimed to investigate patient adherence to face-down positioning (FDP) and non-supine positioning (NSP) following vitrectomy with gas tamponade for treating macular holes (MHs).MethodsNursing records of 92 patients who underwent vitrectomy with gas tamponade for small-diameter (diameter < 400 μm) MHs during April 2016–June 2017 were examined. Forty-seven and 45 patients were instructed to maintain FDP and NSP (FDP and NSP groups), respectively. Patient adherence was evaluated seven times a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…One is the gas tamponade for which some authors have suggested additional gas injection in case of non-closure at first attempt 16 . In addition to that Emi Morimoto showed that 50% of the patients are non-compliant regarding face down posturing 17 . Some studies have indicated the non-supine posturing was equally good for macular hole closure 18 .…”
Section: Discussionmentioning
confidence: 91%
“…One is the gas tamponade for which some authors have suggested additional gas injection in case of non-closure at first attempt 16 . In addition to that Emi Morimoto showed that 50% of the patients are non-compliant regarding face down posturing 17 . Some studies have indicated the non-supine posturing was equally good for macular hole closure 18 .…”
Section: Discussionmentioning
confidence: 91%
“…In addition to larger numbers, a longer follow-up period is needed to correlate factors with clinical outcomes. 9 Despite its limitations, this pilot study presents some novel angles including the use of a compact wireless position sensor in an ophthalmic shield platform that obviates the use of more cumbersome or potentially uncomfortable head gear or bands. This device showed it could reliably record the head position every 5 minutes and without any interruption, which is useful if any live sensory feedback is going to be used in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to larger numbers, a longer follow-up period is needed to correlate factors with clinical outcomes. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone oil tamponade is employed for those cases. Furthermore, in rare cases, the face-down position can also cause systemic complications such as pulmonary embolism, thrombophlebitis, and ulnar nerve palsy [5][6][7] . To overcome these problems, recent studies have reported that a strict face-down position may not be necessary [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%